Multiculturalism, Politics Identity, and Lifestyle of Today's Youth Clothing - Hikmawati, Hanifah; Salamah, Sholihatus (International Journal on Higher Education Issues, 2025)
This study aims to explain multiculturalism which reflects diversity culture in a society that enables the occurrence interaction as well as assimilation values and style life . Politics identity emphasize How individuals or groups use identity culture as a tool for shaping position social and political them . In the context of youth, this phenomenon is reflected in election style dressing that is not only influenced by global trends , but also by values local and specific group identities . Today's youth utilise clothing as a medium of expression self , symbol resistance , or even form affirmation to identity his group . With the existence of the influence of social media and culture popular , development style These clothes are increasingly dynamic and reflective complexity interaction between multiculturalism , politics identity , as well as current globalization . Therefore that , research about connection third This aspect is important to understand how young people interpret identity and diversity in modern life . Changes have an impact on the lifestyle of young people in terms of clothing. Young people tend to choose clothing styles based on what they see on social media sites, for example fashion trends for cewek kue, cewek bumi, and cewek mamba . This study uses method qualitative descriptive approach studies bibliography , which is based on the collection and analysis designed to produce appropriate ideas. The results of this study explain that there is an influence between lifestyle in dressing and identity politics for young people to appear modern.